Rancang Bangun Alat Pengering Udang Ebi Tenaga Biomass Di Kecamatan Sungai Kunyit - Junaidi, J; Kurnianto, Rudi (ELKHA : Jurnal Teknik Elektro, 2016)
Abstract– Most of the people in the district of Sungai Kunyit are engaged in the business of seafood including udang ebi. Udang ebi's monthly production in this district reached 5000 kg. Although the potential of udang ebi processing in Sungai Kunyit dsitrict is quite large, it's benefits still not improve the lives and welfare of the local fishermen. The low of education level may directly affect welfare of society that in general are still categorized as underprivileged families. Partners in this community service activities are the drying group of udang ebi in the territory of Sungai Kunyit district. The partners were Usaha Bahari Terpadu and Karya Bersama. These drying groups of udang ebi are generally running their business still use the traditional way by relying on the natural sunlight for drying udang ebi catches. So that during the rainy season, where the sun shines not too good and often cloudy, their income declined up to 40%. The above problem encouraged the team Community Services in the Sungai Kunyit district to conduct socialization and pilot project in construction drying oven for udang-ebi. Through this science and technology for Society (Ibm) program funded by Directorate of Research and Community Service (DP2M), it is expected to give significant effect on improvement in live and welfare of the local fishermen, especially drying group of udang-ebi, and finally increases the health, education and economic levels of society in general. Keywords– Nelayan, Ebi, Mesin pengering, Biomass.